2011
DOI: 10.1002/eji.201041324
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stem cells respond to native but not oxidized damage associated molecular pattern molecules from necrotic (tumor) material

Abstract: Necrosis is a characteristic feature of advanced solid tumors. Released necrotic factors, also referred to as damage associated molecular patterns (DAMPs), are known to critically impact the tumor microenvironment by enhancing angiogenesis or influencing the immune response. We have recently shown that DAMPs can act as chemoattractants and activators of granulocytes. We demonstrate that necrotic material from both normal and tumor cells promotes proliferation and trafficking of human mesenchymal stem cells (MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 24 publications
1
68
0
Order By: Relevance
“…This observation appears to be in conflict with previous studies. 36,45,46 Interestingly, the HMGB1-driven migratory responses of MSC in these studies have either been independent of RAGE 36,46 or the type of receptor has not been assessed, 45 which could imply a possible role of HMGB1/ CXCL12 complexes. On the other hand, RAGE-mediated chemoattractive activity of HMGB1 has been documented for other stem and progenitor cells, including endothelial progenitor cells, 37 as well as for progeny of MSC-like smooth muscle cells 47 and fibroblasts.…”
Section: Migration Of Msc Towards Recombinant Hgf Was Inhibitedmentioning
confidence: 91%
“…This observation appears to be in conflict with previous studies. 36,45,46 Interestingly, the HMGB1-driven migratory responses of MSC in these studies have either been independent of RAGE 36,46 or the type of receptor has not been assessed, 45 which could imply a possible role of HMGB1/ CXCL12 complexes. On the other hand, RAGE-mediated chemoattractive activity of HMGB1 has been documented for other stem and progenitor cells, including endothelial progenitor cells, 37 as well as for progeny of MSC-like smooth muscle cells 47 and fibroblasts.…”
Section: Migration Of Msc Towards Recombinant Hgf Was Inhibitedmentioning
confidence: 91%
“…We recently demonstrated, in a DC/ lymphocyte coculture assay, the immunosuppressive capacity of S100A4, S100-pulsed DCs also induced regulatory T cells that suppressed lymphocyte proliferation in allogeneic cocultures (3). We demonstrated that oxidation significantly reduces the bioactivity of lysed cells on MSCs (2). In addition to HMGB1, we have now identified S100A4 as another oxidation-sensitive DAMP that plays a crucial role in the biologic activity of necrotic material.…”
Section: Discussionmentioning
confidence: 79%
“…We have recently shown that necrosis-associated factors (DAMPs) from lysed cells can also promote the proliferation of MSCs (2), but once necrotic material was oxidized or preincubated with soluble RAGE, nominally blocking RAGE ligands (including S100A4 and HMGB1), the enhanced proliferative effect was significantly diminished (2).…”
Section: S100a4 and Ua Impact Msc Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors act as “danger” signals recruiting inflammatory cells, inducing inflammation (cytotoxic environment) on the one hand, but promoting wound healing processes (immunosuppressive environment), on the other. While wound healing is itself a self‐limiting process, advanced solid tumors—being “addicted to death”1—perpetually release DAMPs which promote recruitment of MSCs,2 enhance angiogenesis, and limit immunity 3. Thus, the tumor coopts the regenerative capacity of the host1, 4 resulting in tumor's own survival and proliferation.…”
Section: Introductionmentioning
confidence: 99%